Literature Review : Pengaruh Penerapan Model Pembelajaran Collaborative Problem Solving Terhadap Kemampuan Berpikir Kritis Matematis Siswa - Nur Syafina, Nur Syafina; Aisyah Nur Syam, Aisyah Nur Syam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The application of the Collaborative Problem Solving (CPS) learning model in mathematics learning has shown great potential in improving students' mathematical critical thinking skills. This study aims to comprehensively review scientific articles discussing the application of CPS in mathematics learning and its impact on students' critical thinking skills in the 2019-2025 period. The method used is a systematic literature review by searching through Google Scholar, databases using the keywords "Collaborative Problem Solving", "Critical Thinking", "Mathematical Thinking", and "Mathematics Education". From the results of the review of 30 relevant articles, it was found that most studies showed that CPS improves mathematical critical thinking skills through collaboration between students in solving complex mathematical problems. In addition, several studies integrated CPS with other approaches such as Problem Based Learning (PBL) and Project-Based Learning (PjBL), which have also been shown to strengthen students' critical and creative thinking skills. The analysis shows that CPS consistently improves students' abilities in analyzing word problems, formulating problem-solving strategies, and applying mathematical concepts in real-world contexts. Based on the results of the literature review, it can be concluded that the implementation of CPS can have a significant positive impact on the development of students' mathematical critical thinking skills, which are essential in mathematics learning at the secondary education level.